2009
DOI: 10.1007/s00432-009-0690-5
|View full text |Cite
|
Sign up to set email alerts
|

Age as a prognostic factor for patients with osteosarcoma: an analysis of 438 patients

Abstract: Age at diagnosis does not appear to be a significant independent prognostic variable for overall survival or disease-free survival in patients with osteosarcoma. Although our data indicate that patients in the fifth decade and older fare worse than younger patients, other variables such as tumor necrosis, tumor extension, and tumor location are likely responsible for the observed decline in overall survival and disease-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
57
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 23 publications
8
57
1
Order By: Relevance
“…Consistent with prior reports, tumor size, 7,14,31,32 anatomic site, 7,13,15,32 and metastatic status at presentation 7,10,31,33,34 were strong determinants of survival outcome. After adjusting for these parameters, tumor subtype retained independent prognostic significance.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with prior reports, tumor size, 7,14,31,32 anatomic site, 7,13,15,32 and metastatic status at presentation 7,10,31,33,34 were strong determinants of survival outcome. After adjusting for these parameters, tumor subtype retained independent prognostic significance.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to the situation involving advancing age, prior research on osteosarcoma revealed that tumors in the axial skeleton and large tumors were associated with a poor prognosis 5,[8][9][10]16,21 . The inferior oncologic results in these cases can be partially explained by the difficulty in performing surgical resection and obtaining adequate margins 3,5 .…”
mentioning
confidence: 89%
“…Many previous studies have revealed an association of increasing age with a poorer prognosis in patients with osteosarcoma [5][6][7]10,16,17 . However, there is substantial uncertainty and debate regarding whether age itself is a risk factor or is simply a surrogate for other, more important, aspects of the disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar report by Hagleitner et al [13] in Netherland also concluded that younger patients had significantly better outcome than older patients, but their statement was depend on OS and EFS rates of 5-year, which means that longer-term follow-up such as our 10-year OS and EFS rates might have produced different outcomes. In a study by Hartling et al [14] at M.D. Anderson Cancer Center, patient group of aged 21 -40 years presented relatively better OS rate and less RR (risk ratio) than the other age groups, although these were not statistically significant values and they concluded that age at diagnosis did not seem to be a significant prognostic factor.…”
Section: Discussionmentioning
confidence: 95%